Evaluation of different storage structures and monitoring of storage molds in onion genotypes for managing postharvest diseases - KRISHNAPRASAD and VEEREGOWDA, M.K. NAIK*, K. RAJU, G.S. DEVIKA RANI (Indian Phytopathology, 2008)
Different onion storage structures were evaluated for black and blue mold occurrence in onion. Among them bottom ventilated single row storage structure with thatched roof was the best one for small farmers due to low severity (15-25%) of onion molds and low cost of construction. The modified bottom ventilated double row storage structure with asbestos roof was the best one for big farmers and traders because of high capacity with low spoilage. Ten onion genotypes when evaluated under storage condition by artificial inoculation using pin-prink method and monitored for mold infection upto 90 days after storage (DAS) the genotypes, Arka Kalyan and Arka Pitamber showed less severity (